The historical ecology of vegetation change in Dovedale (Derbyshire and Staffordshire) - Robinson, Anthony (2018)
This dissertation describes a study of historical vegetation change in Dovedale. Within the framework of historical ecology, and with a focus on the use of postcards, it uses a combination of documentary research and fieldwork. The aims of the study are to examine the change since about 1860, and consider its implications, while evaluating the use of postcards as a research method.